A transgenic mouse line with a 58 kb fragment deletion shows skeletal defects - Ahmed Alamoudi; Dina Husein; Yoshio Ohyama; Angela Chen; Hanna Mochida; Yoshiyuki Mochida (Scientific Reports)
Abstract Previously, a transgenic mouse line lacking a 58 kb fragment deletion including the upstream and exon1 of Fam20a gene (58 kb deletion mouse) was generated and showed growth retardation. The aim of this study was to characterize the skeletal phenotype of the homozygous 58 kb deletion mouse (58 kb-/-). Our results showed that body size and bone length of the 58 kb-/- mice were smaller than those of wild-type (WT) mice. The microcomputed tomography (µCT) analyses of trabecular and cortical bones in the 58 kb-/- displayed lower bone volume, thinner trabeculae and thinner bone cortex as compared to WT. Histological examination of the 58 kb-/- growth plate demonstrated disorganized chondrocyte zones and extended hypertrophic zone. The qPCR results showed downregulation of several osteoblast differentiation markers in the 58 kb-/- long bone. Immunohistochemical examination demonstrated reduced chondrocyte proliferation, apoptosis and increased collagen X expression in the 58 kb-/- growth plate. Our data showed a lower number of osteoblasts and osteoclasts in the 58 kb-/- as compared to WT. In vitro cell culture study demonstrated the 58 kb-/- showed a lower number of bone marrow stromal cells and osteoprogenitors. The extent of matrix mineralization was impaired in the 58 kb-/- osteoblast cultures. In conclusion, endochondral ossification defects and reduced number of osteoblasts and their precursors led to the bone phenotype in the 58 kb-/-, indicating that the genes deleted in this 58 kb likely play an important role in skeletal development.